Circulating long non‐coding RNAs NRON and MHRT as novel predictive biomarkers of heart failure. Issue 9 (14th March 2017) - Xuan, Lina; Sun, Lihua; Zhang, Ying; Huang, Yuechao; Hou, Yan; Li, Qingqi; Guo, Ying; Feng, Bingbing; Cui, Lina; Wang, Xiaoxue; Wang, Zhiguo; Tian, Ye; et al.
Abstract: This study sought to evaluate the potential of circulating long non‐coding RNAs (lncRNAs) as biomarkers for heart failure (HF). We measured the circulating levels of 13 individual lncRNAs which are known to be relevant to cardiovascular disease in the plasma samples from 72 HF patients and 60 non‐HF control participants using real‐time reverse transcription‐polymerase chain reaction (real‐time RT‐PCR) methods. We found that out of the 13 lncRNAs tested, non‐coding repressor of NFAT ( NRON ) and myosin heavy‐chain‐associated RNA transcripts ( MHRT ) had significantly higher plasma levels in HF than in non‐HF subjects: 3.17 ± 0.30 versus 1.0 ± 0.07 for NRON ( P < 0.0001) and 1.66 ± 0.14 versus 1.0 ± 0.12 for MHRT ( P < 0.0001). The area under the ROC curve was 0.865 for NRON and 0.702 for MHRT . Univariate and multivariate analyses identified NRON and MHRT as independent predictors for HF. Spearman's rank correlation analysis showed that NRON was negatively correlated with HDL and positively correlated with LDH, whereas MHRT was positively correlated with AST and LDH. Hence, elevation of circulating NRON and MHRT predicts HF and may be considered as novel biomarkers of HF.